Metode Menebak Kontekstual versus Pembelajaran Berbasis Proyek: Studi Perbandingan Respon dan Kesulitan Siswa dalam Belajar Bahasa Inggris - Ida Lisdawati; Nisa El Fauziah, Ula; P. Bhuana, Gartika (English Education Department of STKIP Pasundan, 2023)
ABSTRACT Students needed to gain comprehension of the material to participate in reading activities. Many students still struggled to read English-language texts, nevertheless. They encountered unfamiliar words regularly. Consequently, contextual guessing and project-based learning emerged as a method that students may use to deduce the text. The goals of this study were to: (1) ascertain how students felt about using the technique to raise their reading comprehension levels; and (3) look into the challenges that students faced when using the technique to understand the text. An explanatory sequential design with mixed methodologies was employed in the study. The instruments included an open-ended interview, a closed-ended questionnaire, and a multiple-choice exam. Thirty-two students from one of the junior high schools in Cimahi served as the research subjects. These two conclusions are the result of this research: The use of the contextual guessing technique and project-based learning had an impact on students' reading comprehension, according to the following findings: (1) the questionnaire data; and (2) the interview data, which indicated that students' positive responses to the use of the contextual guessing technique in teaching reading comprehension were based on two factors: (1) a lack of vocabulary and (2) weak English proficiency.